Incidence, predictors, management and outcomes of coronary perforations. Issue 1 (12th October 2018) - Shaukat, Arslan; Tajti, Peter; Sandoval, Yader; Stanberry, Larissa; Garberich, Ross; Nicholas Burke, M.; Gössl, Mario; Henry, Timothy; Mooney, Michael; Sorajja, Paul; Traverse, Jay; Bradley, Steven M.; et al.
Abstract: Objectives: We examined the contemporary incidence, types, predictors, angiographic characteristics, management and outcomes of coronary perforation. Background: Coronary perforation is a rare, but important, complication of percutaneous coronary intervention (PCI). There is lack of data on perforations stratified as large and distal vessel perforations. Methods: Retrospective, observational cohort study of all patients who underwent PCI at a high volume, tertiary hospital between the years 2009 and 2016. Angiograms of all coronary perforation cases were reviewed to determine the mechanism, type, and management of perforation. Risk‐adjusted periprocedural complication rates were compared between patients with and without coronary perforation. One‐year mortality outcomes of patients with large vessel vs. distal vessel perforation were also examined. Results: Coronary perforation occurred in 68 of 13, 339 PCIs (0.51%) performed during the study period: 51 (75%) were large vessel perforations and 17 (25%) distal vessel perforations. Most (67%) large vessel perforations were due to balloon/stent inflation, whereas most (94%) distal vessel perforations were due to guidewire exit. Patients with coronary perforations had significantly higher risk for periprocedural complications (adjusted odds ratio 7.57; 95% CI: 4.22–13.50; P < 0.001). Only one patient with large vessel perforation required emergency cardiac surgery, yet in‐hospital mortality was high with both large vessel (7.8%) and distal vessel (11.8%) perforations. Conclusions: Coronary perforation is an infrequent, but potentially severe PCI complication. Most coronary perforations are large vessel perforations. Although coronary perforations rarely lead to emergency cardiac surgery, both distal vessel and large vessel perforations are associated with high in‐hospital mortality, highlighting the importance of prevention.